2019
DOI: 10.1038/s41598-019-40598-3
|View full text |Cite
|
Sign up to set email alerts
|

Microwave treatment regulates the free volume of rice starch

Abstract: The aim of this work was to investigate the role of microwave parameters and moisture content on the free volume (FV) changes of rice starch by positron annihilation lifetime spectroscopy analysis (PALS) and to explore the potential relationship between the changes of FV and physicochemical properties of rice starch. Microwave heating and water molecules lead to the increasing of FV of starch. However, this result is largely influenced by the plasticization of water molecule. The anti-plasticization caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…(2017) and Yan et al . (2019). Having a higher T g for food powders is important for maintaining stability during storage (Ramakrishnan et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017) and Yan et al . (2019). Having a higher T g for food powders is important for maintaining stability during storage (Ramakrishnan et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…MW pretreatment caused an increase in the T g values of the mucilage samples and this increase was more significant when the MW pretreatment time was 7.5 min. The reason of this phenomena could be related to the transition of cytoplasmic bulk water to bound water as stated by Zhao et al (2017) and Yan et al (2019). Having a higher T g for food powders is important for maintaining stability during storage (Ramakrishnan et al, 2018).…”
Section: Glass Transition Temperature (T G )mentioning
confidence: 99%
“…An early study showed that microwave heating (60 min) had no significant effect on the digestibility of waxy and non-waxy rice starches (with 20% water content), but changed their viscosity [17]. Also for rice starch, it was reported that microwave treatment made the amorphous lamellae more compact [18] and resulted in the double helices of amylopectin becoming more optimally or densely packed and thus more ordered crystalline lamellae [19]. The effect of microwave on the amorphous and double-helical structures of starch granules was considered to be mainly related to the rapid heating effect of microwave [19].…”
Section: Introductionmentioning
confidence: 99%